Effects of different empty fruit bunch (EFB) composting periods on the productivity of volvariella volvacea - Abd Rauf, Noratika (2017)
Volvariella volvacea, also known as the paddy straw mushroom, belongs to the family Pluteaceae. It was first cultivated in China as early as 1822. Referred as a ‘warm mushroom’ because of its ability to grow at high temperature, it is also a fast-growing mushroom compared to other mushrooms. Volvariella volvacea was proven suitable to be cultivated using empty fruit bunch (EFB) of oil palm compared to paddy straw as a cultivation substrate. In previous research, there is only one study of improving the yield quantity of Volvariella volvacea by using various cultivation substrates; paddy straw, cotton waste, banana leaves, sawdust and EFB. With the same purpose of improving yield production, this study focuses on determining the most suitable number of days of composting EFB to be used in the cultivation of Volvariella volvacea. Previously, the common number of days of composting EFB used by mushroom growers is nine days, but there are no studies that prove nine is the best number of days for composting EFB. In this study, three replicates of each different number of days of composting EFB were conducted. The composting plots were arranged using Randomized Complete Block Design (RCBD) and were conducted under favorable conditions for the cultivation of mushrooms cultivation. Six, nine and twelve day of composting EFB were selected to determine the validity of this research, which was conducted in outdoor cultivation for practical purposes in achieving the main objectives of this study. Both yield production and biological efficiency (BE%) of Volvariella volvacea are used as an indicator in this study and for determining the most suitable days of composting EFB that can be used. The values of the yield production and biological efficiency are collected and processed using t-test. The results show that twelve day of composting EFB give the highest yield production and biological efficiency but it shows no significant difference in both result indicator among the different composting periods of EFB substrate for Volvariella volvacea cultivation. The studies findings reveal an opportunity for commercial of Volvariella volvacea mushroom especially in saving time of composting EFB as the cultivation substrate.